2012
DOI: 10.1017/s1431927612013359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Radiation, Photosynthetically Active Radiation and Artificial Ultraviolet Radiation-B on the Chloroplast Organization and Metabolism ofPorphyra acanthophoravar.brasiliensis(Rhodophyta, Bangiales)

Abstract: We undertook a study of Porphyra acanthophora var. brasiliensis to determine its responses under ambient conditions, photosynthetically active radiation (PAR), and PAR+UVBR (ultraviolet radiation-B) treatment, focusing on changes in ultrastructure, and cytochemistry. Accordingly, control ambient samples were collected in the field, and two different treatments were performed in the laboratory. Plants were exposed to PAR at 60 μmol photons m-2 s-1 and PAR + UVBR at 0.35 W m-2 for 3 h per day during 21 days of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…In a previous study using Sargassum cymosum C. Agardh as a biological model to evaluate the combined effects of UV radiation and salinity, Polo et al (2014a) found that UVA and UVB together in low doses such as the ones used herein stimulated the growth rate, leading to an increase in the amount of mitochondria, which could support the metabolic energy demand required for this process. Indeed, studies with different algal species at low doses of UV radiation show that the UV level modulates diverse physiological responses besides growth through up-or downregulation, such as induction of Chl a, phenolic compounds and antioxidant activity (Polo et al 2014a), alteration in putrescine/spermidine ratio (Polo et al 2014b), variation of photosynthetic performance and accessory pigments (Simioni et al 2014, Schmidt et al 2015, and ultrastructural organization (Bouzon et al 2012, Pereira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study using Sargassum cymosum C. Agardh as a biological model to evaluate the combined effects of UV radiation and salinity, Polo et al (2014a) found that UVA and UVB together in low doses such as the ones used herein stimulated the growth rate, leading to an increase in the amount of mitochondria, which could support the metabolic energy demand required for this process. Indeed, studies with different algal species at low doses of UV radiation show that the UV level modulates diverse physiological responses besides growth through up-or downregulation, such as induction of Chl a, phenolic compounds and antioxidant activity (Polo et al 2014a), alteration in putrescine/spermidine ratio (Polo et al 2014b), variation of photosynthetic performance and accessory pigments (Simioni et al 2014, Schmidt et al 2015, and ultrastructural organization (Bouzon et al 2012, Pereira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Phycobiliproteins, the characteristic reddish pigment of red macroalgae, are the most sensitive antenna pigment, localized externally to the reaction center and the first photosynthetic pigment to decrease in concentration under light stress (Bouzon et al 2012, Gouveia et al 2013. Under the most extreme condition of this experiment (day 7, 1000 μmol photons m −2 s −1 ), the apical portions of G. tenuifrons were completely yellowish (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Control and treated samples were attached on slides and sealed using colorless nail polish. A Leica HCX PLAPO lambda 63x/1.4-0.6 oil immersion objective was fitted on the inverted fluorescent microscope [ 32 ]. Chloroplast auto-fluorescence was observed at 488 nm laser wavelength excitation with emission spectrum from 639 nm to 701 nm [ 33 ].…”
Section: Methodsmentioning
confidence: 99%